Gene expression of the oil palm transcription factor EgAP2-1 during fruit ripening and in response to ethylene and ABA treatments. - Omidvar, Vahid; Abdullah, Siti Nor Akmar; Ebrahimi, Mahdi; Ho, Chai Ling; Mahmood, Maziah (Springer Netherlands, 2013)
A cDNA encoding an ERE-binding protein (EgAP2-1) was isolated from the oil palm fruit mesocarp treated with ethylene using yeast one-hybrid assay. EgAP2-1 belongs to the AP2 subfamily of the APETALA2/ethylene-responsive factor (AP2/ERF) proteins and contains two highly conserved AP2/EREBP DNA-binding domains (DNA-BD). Sequence comparison of EgAP2-1 with other AP2 proteins revealed high conservation of the two AP2/EREBP domains and linker region among these proteins. Its protein was localized to the nucleus of onion epidermis cells and showed ERE-specific binding, transcriptional activation, and transactivation properties in yeast and in vitro. Its mRNA was highly expressed in oil palm mesocarp with elevated levels in ripening fruits but not in leaves and roots. EgAP2-1 was induced in mesocarp in response to ethylene and abscisic acid but not other hormonal stimuli, including methyl jasmonate and salicylic acid, and abiotic stresses including drought, cold, and high-salinity. Our results demonstrate a link between the regulation of EgAP2-1 expression and ethylene- and/or ABA-coordinated control of the fruit ripening and suggest a regulatory role for EgAP2-1 during fruit ripening and development in oil palm.